Post COVID-19 vaccination headache: A clinical and epidemiological evaluation - Ceccardi, Giulia; Schiano di Cola, Francesca; Di Cesare, Marco; Liberini, Paolo; Magoni, Mauro; Perani, Cristiano; Gasparotti, Roberto; Rao, Renata; Padovani, Alessandro (Frontiers in Pain Research, 2022)
Introduction This study aimed to assess the prevalence and clinical characteristics of headaches, in particular secondary headaches. Materials and Methods This observational study was performed at the ASST Spedali Civili of Brescia, Italy. Visits to the Emergency Department (ED) and subsequent hospitalizations regarding a new or worsening headache in the 16 days following the administration of the COVID-19 vaccine between January 2021 and January 2022 were recorded and compared with those of January 2019–January 2020. Results The ratio between ED admissions due to headaches and total ED admissions was significantly higher in 2021 compared with 2019 (4.84% vs. 4.27%; p < 0.0001). Two-hundred and eighty-nine ED headache admissions (10.8% of all ED headache admissions) were time-correlated to the COVID-19 vaccination, of which 40 were hospitalized in order to exclude a symptomatic etiology. At discharge, 32 patients had a diagnosis of benign headache not attributed to any cranial/extracranial disorder and eight patients of secondary headache, whose diagnoses were the following: Headache attributed to cranial and/or cervical vascular disorder (n = 4); headache attributed to nonvascular intracranial disorder (n = 2); headache or facial pain attributed to disorder of the cranium, neck, eyes, ears, nose, sinuses, teeth, mouth, or other facial or cervical structure (n = 1); and painful lesions of the cranial nerves (n = 1). The headache most frequently reported by patients had migraine-like characteristics: the localization was predominantly frontal or temporal, the pain was described as throbbing and severe in intensity and it was frequently accompanied by nausea/vomit, and photo-phonophobia. Over half—regardless of the final diagnosis—of hospitalized patients had a history of primary headaches. Conclusions Following the spread of COVID-19 vaccination, the number of ED admissions due to headaches significantly increased. However, less than 14% of all the ED visits due to a headache time-correlated to the COVID-19 vaccination were actually hospitalized, with most patients documenting a benign headache, possibly related to the generic side effects of the vaccination. Only 8/40 hospitalized patients were diagnosed with a secondary headache. These benign headaches would actually fulfill diagnostic criteria for 8.1 Headaches attributed to the use of or exposure to a substance (ICHD-3), although, at the time being, it does not include vaccines as possible substances. The headache migraine-like characteristics’ reported by most patients could suggest activation of the trigeminovascular pathway by all the cytokines and other pro-inflammatory molecules released following the vaccination.